Causes and Impact of Rework on Residential Construction Project: Examining the causes and consequences of rework in residential construction projects (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Time and cost are very important factor for successful and profitable construction project. Any construction project becomes success when it is finished within estimated cost and Time. Schedule and cost overrun are becoming a headache for owner as well as the other parties involved the project. The major contributor for schedule and cost overrun is rework. Rework has negative impact on the quality of work and on the parties involved in the construction project. This paper discusses about the construction rework, its causes and impacts.